The effectiveness of eating-based mindfulness training on alexithymia and self-differentiation of overweight women - Shariati, Sahar; Abbasi, Ghodratollah; Mirzaian, Bahram (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The prevalence of obesity and overweight is increasing at an alarming rate in Iran, which can bring various psychological consequences for obese people. The purpose of this research was to determine the effectiveness of mindfulness training based on eating on alexythymia and self-differentiation of overweight women. Methods: The current research design was a semi-experimental type of pre-test, post-test and follow-up with a control group. The statistical population in this research included all overweight women of Gonbadkavus city who referred to overweight and obesity treatment clinics in the first half of 2021. From the statistical population of the research, a sample group consisting of 30 overweight women who were selected in a purposeful way and then randomly assigned to two experimental groups (mind-awareness training based on eating) (15 people) and control (15 people) became Then overweight women in the experimental group underwent 8 sessions of 90 minutes each week, one session of mindfulness training based on eating, but the control group did not receive any intervention. The tools of the research were Toronto et al.'s (2007) alexithymia questionnaires and Skowron and Friedlander's (1988) self-differentiation questionnaire. Analysis of variance with repeated measurements and spss software were used to analyze the data. Results: The results showed that there was a significant difference in terms of improving the difficulty of identifying emotions (F=8.16, P